Trifluoro alkyl side chains in the non-fullerene acceptors to optimize the phase miscibility and vertical distribution of organic solar cells. Issue 16 (28th March 2022) - Zhang, Tian; Chen, Haopeng; Li, Chuanfu; Lu, Kun; Zhang, Liting; Shokrieh, Ahmad; Zhang, Jianqi; Lu, Guanghao; Lei, Shengbin; Wei, Zhixiang
Abstract : By introducing the trifluoride group to control the compatibility of the material, the acceptor tends to cluster in the upper part of the active layer, which helps to shorten the exciton transport channel and increase the collection of excitons. Abstract : The invention of Y-series non-fullerene acceptors (NFAs) has made a breakthrough in high-performance organic solar cells (OSCs). However, the morphology optimization of the active layer is still challenging in NFA-based OSCs due to the similar building units of the donor and acceptor. Herein, we propose an NFA molecular structure by introducing trifluoro alkyl side chains to the pyrrole unit of the fused ring dithienothiophen[3, 2- b ]-pyrrolobenzothiadiazole (BTP) core for the first time. Three acceptors with different trifluoro alkyl chains are designed and synthesized, named BTP-BF, BTP-OF, and BTP-DF for the molecules with trifluorobutyl, trifluorooctyl, and trifluorodecyl side chains, respectively. The trifluorodecyl side chains of the BTP-DF molecule can regulate the intrinsic properties of the molecule, which has a significant beneficial effect on the surface energy and the intermolecular interaction. A vertical phase distribution is obtained by pairing BTP-DF with a wide bandgap polymer donor (PTQ10), and the device efficiency can reach as high as 15.14%. These results reveal that introducing trifluoro substitution groups to alkyl side chains is an effective strategy to achieve reduced surface energy and optimal vertical phase distribution, thus facilitating the charge separation and collection to obtain high-performance OSCs.